2018
DOI: 10.3389/fenvs.2018.00065
|View full text |Cite
|
Sign up to set email alerts
|

In Situ X-Ray Tomography Imaging of Soil Water and Cyanobacteria From Biological Soil Crusts Undergoing Desiccation

Abstract: Biological soil crusts (biocrusts) are millimeter-sized microbial communities developing on the topsoils of arid lands that cover some 12% of Earth's continental area. Biocrusts consist of an assemblage of mineral soil particles consolidated into a crust by microbial organic polymeric substances that are mainly produced by filamentous bundle-forming cyanobacteria, among which Microcoleus vaginatus is perhaps the most widespread. This cyanobacterium is the primary producer for, and main architect of biocrusts i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…6 ) as water and organic C availability decreases, it is unclear if the low soil water content during the dry period allows any ongoing enzyme activity. While pockets of increased humidity have been proposed to exist in dry soil ( 5 , 66 ), a study applying in situ X-ray tomography to BSCs from the Moab Desert suggested the absence of such pockets after complete desiccation ( 78 ). However, even the near complete absence of water does not have to be fatal for a microbial cell.…”
Section: Discussionmentioning
confidence: 99%
“…6 ) as water and organic C availability decreases, it is unclear if the low soil water content during the dry period allows any ongoing enzyme activity. While pockets of increased humidity have been proposed to exist in dry soil ( 5 , 66 ), a study applying in situ X-ray tomography to BSCs from the Moab Desert suggested the absence of such pockets after complete desiccation ( 78 ). However, even the near complete absence of water does not have to be fatal for a microbial cell.…”
Section: Discussionmentioning
confidence: 99%
“… Examples of polymeric structures formed by mucilage and extracellular polymeric substances (EPS) in porous media: (a) light microscope image of threads of mucilage (mucilage content = 4.5 mg g −1 [mg dry mucilage per g of particles]) formed across a large pore during drying; (b) light microscope image of cylinder formed between neighboring glass beads (1.7–2 mm in diameter) at intermediate mucilage content (0.7 mg g −1 ); (c) two‐dimensional EPS‐based structures joining quartz grains in intact biocrusts imaged with synchrotron‐based X‐ray tomographic microscopy (Couradeau et al, 2018), where high EPS content resulted in the formation of characteristic structures (red arrows) comparable with those formed by maize mucilage (the blue arrow marks a cyanobacterial bundle with the EPS sheath surrounding the trichomes of Microcoleus vaginatus ); (d) cross‐section through a synchrotron‐based X‐ray tomographic microscopy volume of dry maize mucilage structures in glass beads (bright circles) (mucilage content = 8 mg g −1 ; glass bead diameter = 0.1– 0.2 mm); and (e) three‐dimensional segmentation of dry mucilage structures (red) from (d) that formed interconnected surfaces of ∼1‐μm thickness within the pore space of glass beads (blue). Additional images of mucilage in porous media can be found in Supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting voxel edge length was 1.3 μm. A more detailed description of the procedure can be found elsewhere (Couradeau et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the diverse techniques that are currently used (for details see the review from Baveye et al, 2018), one of the more promising techniques entails microcomputerized X-ray tomography (µCT). It serves as a powerful tool to analyze soil structure, including aggregates and porosity (Zabler et al, 2008;Peth et al, 2014;Couradeau et al, 2018;Quigley et al, 2018;Totsche et al, 2018). The µCT technique may also be used as a non-destructive method to analyze the soil biota, for example, detecting fine roots and micro-fauna (Mooney et al, 2012;Guimarães et al, 2017).…”
Section: Introductionmentioning
confidence: 99%